Knowledge and perception about climate change and human health: findings from a baseline survey among vulnerable communities in Bangladesh. (December 2016) - Kabir, Md; Rahman, Md; Smith, Wayne; Lusha, Mirza; Azim, Syed; Milton, Abul
Abstract Background Bangladesh is one of the countries most vulnerable to climate change (CC). A basic understanding of public perception on vulnerability, attitude and the risk in relation to CC and health will provide strategic directions for government policy, adaptation strategies and development of community-based guidelines. The objective of this study was to collect community-based data on peoples' knowledge and perception about CC and its impact on health. Methods In 2012, a cross-sectional survey was undertaken among 6720 households of 224 enumeration areas of rural villages geographically distributed in seven vulnerable districts of Bangladesh, with total population of 19, 228, 598. Thirty households were selected randomly from each enumeration area using the household listing provided by the Bangladesh Bureau of Statistics (BBS). Information was collected from all the 6720 research participants using a structured questionnaire. An observation checklist was used by the interviewers to collect household- and community-related information. In addition, we selected the head of each household as the eligible participant for an interview. Evidence of association between sociodemographic variables and knowledge of CC was explored by cross-tabulation and measured using chi-square tests. Logistic regression models were used to further explore the predictors of knowledge. Results The study revealed that the residents of the rural communities selected for this study largely come from a low socioeconomic background: only 9.6 % had postsecondary education or higher, the majority worked as day labourer or farmer (60 %), and only 10 % earned a monthly income above BDT 12000 (equivalent to US 150 approx.). The majority of the participants (54.2 %) had some knowledge about CC but 45.8 % did not (p < 0.001). The majority of knowledgeable participants (n = 3645) felt excessive temperature as the change of climate (83.2 %). Among all the respondents (n = 6720), 94.5 % perceived change in climate and extreme weather events. Most of them (91.9 %) observed change in rainfall patterns in the last 10 years, and 97.8 % people think their health care expenditure increased after the extreme weather events. Age, educational qualification, monthly income, and occupation were significantly associated with the knowledge about climate change (p < 0.001). People with higher educational level or who live near a school were more knowledgeable about CC and its impact on health. Conclusions The knowledge level about CC in our study group was average but the perception and awareness of CC related events and its impact on health was high. The most influential factor leading to understanding of CC and its impact on health was education. School-based intervention could be explored to increase peoples' knowledge about CC and necessary health adaptation at community level.